Analisis Penerapan Perencanaan Pajak Penghasilan 21 Sebagai Strategi Penghematan Pembayaran Pajak Perusahaan Pada PT. Duta Agung Jaya - Riska Inayah (Cattleya Darmaya Fortuna, 2023)
PT. Duta Agung Jaya has carried out article 21 ncome tax planning as an effort to efficiently pay corporate ncome tax. Where, taxes are one of the deductions of company ncome, therefore companies need ways that can be used to save the company's tax burden. One way that can be used to streamline the tax burden s by means of Tax Planning. This study aims to find out whether there s a significant difference between corporate ncome tax before and after the application of tax planning n PT. Duta Agung Jaya n saving ncome tax owed. This type of research s descriptive through observation and nterviews. The research data conducted s n the form of primary data. Where primary data s carried out, namely data obtained directly from agencies which are then processed by researchers. The primary data n this study are employee lists, employee payrolls, and financial statements. The results of this study show that article 21 tax planning using the Gross Up method s the most appropriate for companies. The application of Gross Up has proven successful n reducing Corporate ncome Tax.